The evolutionary invisible hand: “Why are we successful? And how do we know we have made an economic error?” - Rossi Mazzoni, João Fernando (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2022)
Book review: POSVANC, Matus. The Evolutionary Invisible Hand - The Problem of Rational Decision Making and Social Ordering over Time. Londres: Palgrave Macmillan